Electrophysiological Correlates of Shot Accuracy of Archers with Different Sports Ranks - Oleg I. Shestakov; Aleksandr M. Pukhov (Northern (Arctic) Federal University, 2024)
The purpose of this study was to establish electrophysiological markers of archers' shot accuracy by correlations between performance and electroencephalogram (EEG) power parameters in athletes of different ranks compared. Materials and methods. The research involved 20 archers shooting the classic bow, who were divided into two groups of 10 subjects each by sports rank: Candidate for Master of Sport and First-Class Sportsman. EEG was recorded using the Encephalan-EEGR-19/26 device (Medikom MTD, Taganrog) in 19 leads according to the 10-20 system. Reference electrodes were placed on the earlobes. Results. It was found that shot accuracy of high-level archers (Candidate for Master of Sport) is marked by an increase in alpha and theta EEG power in the occipito-temporal-frontal regions of the left hemisphere during the preparatory phases of the exercise, and then, by the dissociation of the powers of these frequency ranges while aiming. In contrast, shot accuracy of lower level archers is characterized by a decrease in the power of the main rhythm in the left temporal lead during the first phase of the shot. In the total sample of athletes (regardless of rank) no significant correlations were found in any of the 3365 cases of evaluation of this analytical parameter. Thus, the electrophysiological markers of bow shot accuracy differ between Candidates for Master of Sport and First-Class Sportsmen. The sevenfold greater number of significant correlations (p < 0.05) between EEG parameters and shot accuracy of Candidates for Master of Sport compared to First-Class Sportsmen indicates a high level of development of the Bow Shot functional system of purposeful movements as the skill improves, as well as testifies to the synergism of physiological processes when performing the exercise by Candidates for Master of Sport. The established facts will expand coaches' physiological understanding of the mechanism of purposeful movements in order to objectively predict sports results.